Using MATLAB to Achieve Nanoscale Optical Sectioning in the Vicinity of Metamaterial Substrates by Simulating Emitter-Substrate Interactions - Elsayad, Kareem; Suplata, Marek; Heinze, Katrin (IntechOpen, 2011)
None